1999
DOI: 10.1021/bi982281h
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues Essential for Human Paraoxonase (PON1) Arylesterase/Organophosphatase Activities

Abstract: Human serum paraoxonase (PON1) is a calcium-dependent organophosphatase. To identify residues essential for PON1 activity, we adopted complementary approaches based on chemical modification and site-directed mutagenesis. To detect 45Ca2+ binding to native and chemically modified PON1, we performed nondenaturating gel electrophoresis. The environment of calcium-binding sites was probed using the Ca2+ analogue, terbium. Tb3+ binds to calcium-binding sites as shown by displacement of 45Ca2+ by Tb3+. Binding of Tb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 34 publications
6
57
0
2
Order By: Relevance
“…While da-GAL4/+ (da, daughterless) flies (control flies) did not express PON1, UAS-PON1/da-GAL4 flies (PON1 transgenic flies) expressed PON1, with variable levels of PON1 protein expression observed (PON1R9c > PON1R31 > PON1R1 ≈ PON1R4 > PON1R19) ( Figure 3A). Multiple PON1 bands with differing electrophoretic mobility were observed and are consistent with prior reports of PON1 undergoing N-linked core glycosylation (8,31).…”
Section: P Aeruginosa Lethality In D Melanogaster Is Quorum-sensingsupporting
confidence: 90%
“…While da-GAL4/+ (da, daughterless) flies (control flies) did not express PON1, UAS-PON1/da-GAL4 flies (PON1 transgenic flies) expressed PON1, with variable levels of PON1 protein expression observed (PON1R9c > PON1R31 > PON1R1 ≈ PON1R4 > PON1R19) ( Figure 3A). Multiple PON1 bands with differing electrophoretic mobility were observed and are consistent with prior reports of PON1 undergoing N-linked core glycosylation (8,31).…”
Section: P Aeruginosa Lethality In D Melanogaster Is Quorum-sensingsupporting
confidence: 90%
“…Sixteen of these residues in human PON1 were identified as essential for the hydrolytic activity, and all of them except His-243 and Trp-281 are conserved in rabbit PON3. The two PON1 mutants, W281L and H243K, corresponding to the PON3 sequence, have markedly reduced arylesterase and organophosphatase activity (32,33). This observation may at least in part explain the limited arylesterase and paraoxonase activity of rabbit serum PON3 we observed.…”
Section: Discussionmentioning
confidence: 64%
“…Although the active site of the PON1 has not been established, some residues essential for the hydrolytic 3 C. Watson, personal communication. activity have been identified by both chemical modification and site-directed mutagenesis (32)(33)(34). The chemical modification of tryptophan, histidine, aspartic acid/glutamic acid, or cysteine residues reduced or abolished enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme has two calciumbinding sites: the higher affinity calcium is required for the structural integrity, whereas the lower affinity calcium is involved in catalysis (9). Early mechanistic studies using chemical labeling and site-directed mutagenesis identified several residues that are involved in the phosphotriesterase and esterase activities of human PON1 (10,11). However, because these studies were conducted before the three-dimensional structure of PON1 was known, it was largely unclear whether these amino acids are indeed in the PON1 active site or whether they are involved in substrate binding, Ca 2ϩ binding, or catalysis.…”
Section: Serum Paraoxonases (Pons)mentioning
confidence: 99%